Asuhan Keperawatan pada Pasien Pre-Operasi Hemoroid: Studi Kasus - Veronika Fernanda Dua Hiko; Mey Lona Verawaty Zendrato (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe nursing care for a hemorrhoid patient at the X Regional General Hospital (RSUD X) located in DKI Jakarta by describing the patient's management. The method used is a case study with a nursing process approach through interviews (anamnesis), observation, reviewing documents and analysis of problems. The results showed that the suitability of symptom signs between theory and the clinic, dominated by pain, was influenced by work history. Furthermore, two primary diagnoses are enforced according to the signs and symptoms that arise. The focus of the action was to minimize pain, but it was found that at the end of the evaluation, the pain had not been resolved because the prognosis for hemorrhoids had entered an advanced stage, requiring surgery. In conclusion, implementing nursing care has yet to be effectively carried out due to unequal work time and responsibilities. The primary key to treating hemorrhoids is to examine when things are different or uncomfortable in the anal area. Keywords: Nursing Care, Hemorrhoids, Pre-Operation